Assessment of the reliability and validity of a novel point-of-care fibrinogen (F-Point) device against an industry standard at fibrinogen levels >2 g/L in non-haemorrhage scenarios. (August 2020) - Katz, R.; Efremov, V.; Mooney, C.; El-Khuffash, A.; Heaphy, L.; Cosgrave, D.; Loughrey, J.; Thornton, P.
Highlights: Fibrinogen level is a predictor of progression to severe postpartum haemorrhage. This device is a novel point-of-care method to test fibrinogen in whole blood. The F-Point device is valid and reliable at fibrinogen levels as low as 2 g/L. Abstract: Introduction: A diagnostic accuracy study assessing the reliability and validity of a novel plasma fibrinogen point-of-care (F-Point) device compared with the von Clauss method of assay. Methods: Forty-one women presenting for elective caesarean delivery and 43 non-pregnant female patients presenting for elective gynaecological surgery were recruited to assess agreement at normal fibrinogen levels (elective gynaecological cohort) and high fibrinogen levels (elective caesarean section cohort). Validity was assessed by comparing the F-Point results with the gold standard of von Clauss fibrinogen assay performed on the ACL Top 500. Reliability (test–retest) and validity were assessed using the intraclass correlation to control for operator variance (two-way random absolute agreement method), presented as intra class correlation coefficients (ICCs) and 95% confidence interval, and Bland-Altman analysis, presented as mean bias and 95% limits of agreement and coefficient of variation (COV). Results: The results demonstrated a high test–retest reliability demonstrated in the paired F-Point measurements with an intraclass correlation coefficient (ICC) of 0.95, a bias of 0 (-00.69 to 0.69) and a COV of 9%. Similarly, there was acceptable agreement demonstrated between F-Point and von Clauss assay with an ICC of 0.91, a bias of −0.1 (−0.96 to 0.75) and a COV of 11%. Conclusions: Our novel plasma fibrinogen point-of-care device has been shown to be reliable and valid when testing fibrinogen levels as low as 2 g/L. Future studies investigating the correlation at lower fibrinogen levels, for example during haemorrhage and in patients with coagulopathies, are required.